Optimizing MSME Revenue Through Digital Marketing in Perk. Bukit Lawang Village - Enika Diana Batubara; Azulaidin A; Yenni Ramadhani Harahap; Sariyanto S; Syaharman S; Nursidin N (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. The existence of MSMEs contributes to regional economic development, particularly in efforts to encourage an increase in per capita income and income distribution in local areas. One of the most fundamental problems faced by MSMEs is their relatively low productivity, which is caused by the low quality of human resources, especially in the areas of management, organization, mastery of technology, and marketing, as well as the relatively low level of entrepreneurial competence compared to large enterprises. Digital marketing is the application of digital technology in marketing activities and the development or adjustment of marketing strategies by companies. The main focus of continuous efforts to improve individuals’ quality of life is the income generated by MSMEs in Indonesia, particularly in Perk. Bukit Lawang. The problems faced by MSMEs in Perk. Bukit Lawang include the low percentage of businesses utilizing digital marketing, which has not kept pace with the rapid development of the internet, and the lack of necessary skills among some MSME actors to implement digital marketing. Based on these issues, the purpose of this community service activity is to examine how digital marketing helps increase MSME sales revenue in Perk. Bukit Lawang, how digital applications are utilized to advertise products in an effort to increase MSME income, and how digital marketing affects overall sales revenue in Perk. Bukit Lawang.